Cubic Trigonometric Spline for Solving Nonlinear Volterra Integral Equations - Hasan, Nabaa N.; Nasif, Majid R. (Iraqi Journal of Science, 2019)
In this paper, cubic trigonometric spline is used to solve nonlinear Volterra integral equations of second kind. Examples are illustrated to show the presented method’s efficiency and convenience.